Investigating Environmental Governance Impact on Financial Performance: Role of Company Size in Indonesian Palm Oil Firms - Ika Sulistyawati, Ardiani; Mohammed Sultan Saif, Gehad; Himmawan Dwi Nugroho, Arief (Analisis Data Innovation, 2024)
Objective: Drawing up on naturalistic intelligence, the New Environmental Paradigm and environmental sensitivity concepts, this paper aims to investigate their relationships among high school students in terms of differences regarding significant connections of these relations hiop with each other within limits occured by socio-demographic variables through considering substantial environments from context-based higher education oriented phenomenon.Methods: We employed a quantitative approach using path analysis to test the direct and indirect effects of naturalistic intelligence, NEP on ESI. Among students responses were collected using a validated questionnaire which was statistically analyzed to find the significance of relations.Finding: A significant positive correlation existed between the New Environmental Paradigm and environmental sensitivity, but did not find a significant correlation of naturalistic intelligence with it. Results indicate that instilling a pro-environmental attitude is essential in increasing environmental sensitivity to adolescents.Novelty: This study presents a novel perspective by emphasizing the New Environmental Paradigm's role in shaping high school students' environmental attitudes, advocating for value-based education over mere skill enhancement.Conclusion: Our findings underscore the importance of instilling environmentally friendly values and attitudes, rather than just naturalistic skills when designing educational programs. Educators can cultivate environmental citizens ready to meet current challenges by including experiential learning with critical thinking into curricula.